Pengembangan Sistem Visualisasi Access Log untuk Mengetahui Informasi Aktivitas Pengunjung pada Sebuah Website - Rani Andriani; Eko Sakti Pramukantoro; Mahendra Data (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Access log record all requests that processed by the web server. Access log is a file that contains an important line about website visitors. However, access log data is still in the form of raw data so it is difficult to read and analyzed to get activity information of website visitors on a website. In this research, the solution offered is to make a web-based application that can be used as a tool for knowing visitors' activity information on a website using access log data from an apache server. The data of access log will be parsed and the result data of the parsed access log will be saved into the MySQL database. Then this data is filtered by using a specific query in MySQL for later visualized by the application to the form of graphics or tables for further analysis. Based on the results of this study, Access Log Visualizer has been able to parse access logs by using regex and retrieve the access log data from the database by using MySQL query and display the visualization of the data access log, so that this system can process access log data for knowing activity information of website visitors on a website.